Realitas dan Tatanan Urban Kota-Kota di Jepang - Ellisa, Evawani (UI Scholars Hub, 2009)
Despite the highly praised for technology achievements and prosperities, the morphology and appearance of Cities in Japan are often criticized as dull, uninteresting, brutal, and chaos. The question is, how do cities in Japan gain stability while the reality of the urban condition is in a chaos? Is there something behind the chaos that makes urban dwellers of Japanese cities able to relatively live comfortably and safely? This paper analyses some aspects which shaped Japan urbanism, from disorderly addressing system to the speed of building transformations that considerably high. Findings on the hidden orders behind the chaos of Japanese cities reveal an understanding that the spatial and physical chaos of a dense city are not always identified as a social chaos.